2020
DOI: 10.4317/medoral.23482
|View full text |Cite
|
Sign up to set email alerts
|

One-year implant survival following lateral window sinus augmentation using plasma rich in growth factors (PRGF): a retrospective study

Abstract: Background: The aim of this study was to assess one-year implant survival after lateral window sinus augmentation using PRGF combined with various bone grafting materials. Material and Methods: This was a retrospective chart review and radiographic analysis of patients that had undergone lateral window sinus augmentation with PRGF and had dental implants placed at least 6 months post augmentation. All implants included were followed up for at least one year after placement. Demographic, sinus and implant relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 29 publications
(51 reference statements)
1
5
0
Order By: Relevance
“…Studies have shown that the survival rate of implants placed after maxillary sinus augmentation with bone grafts is 95.8%. 11 The aggregated results in this study of lateral and crestal sinus lift are in agreement with published data (96.61%). Despite the difficulties of the intraoperative diagnosis of possible perforation of the sinus membrane related to the crestal approach, successful osseointegration rates in the studied group were high -99.8%).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Studies have shown that the survival rate of implants placed after maxillary sinus augmentation with bone grafts is 95.8%. 11 The aggregated results in this study of lateral and crestal sinus lift are in agreement with published data (96.61%). Despite the difficulties of the intraoperative diagnosis of possible perforation of the sinus membrane related to the crestal approach, successful osseointegration rates in the studied group were high -99.8%).…”
Section: Discussionsupporting
confidence: 92%
“…9,10 Although complications such as infection, sinusitis, membrane perforation, and graft displacement may occur during the procedure, the success rate of the sinus lift is generally high, with implant survival rates ranging from 92.6% to 98.6%. 11,12…”
Section: Introductionmentioning
confidence: 99%
“…(22) Although minor perforations occurred in 5 of 20 sinuses (25%) in the present study, no signs or symptoms of infection involving maxillary sinuses or grafts were observed in the follow-up period. In a recent similar study by Dragonas et al, (17) using PRGF mixed with bovine bone and lateral window sinus augmentation procedure, 36% of the sinuses included had Schneiderian membrane perforation during sinus augmentation; yet this was not associated with implant failure in their study. The membrane, being redundant on its superior reflection, is usually self-sealing.…”
Section: Discussionmentioning
confidence: 81%
“…The increased bone height was 8.78 mm after 6 months period which was approximately four times the RRH. Dragonas et al (17) reported mean initial ridge height of 3.9 mm and ridge height of 15.64mm after lateral window sinus augmentation. The bone height increase in their study was 11.73mm after 6 months from the graft surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation